KNOWLEDGE AND ATTITUDES OF UNIVERSITY STUDENTS OF COSTA RICA ABOUT HIV/AIDS - Salas Chaves, Pilar (2012)
An anonymous survey was conducted to students enrolled in the University of Costa Rica in order to identify the level of knowledge about HIV-aids. It was managed to collect a total 497 questionnaires, during the school year 2008. Respondents considered high-risk mechanisms of transmission of HIV through needle, contaminated needles and sexual intercourse with an infected person without the use of condoms. The results show that students obtained a note of 65,5 and we found no differences in the qualifications obtained by the interviewees, by sex or age. It recommends an education program on prevention of HIV-aids.